PENGEMBANGAN INSTRUMEN ASSESSMENT FOR LEARNING (AFL) PADA MATERI KEKONGRUENAN DAN KESEBANGUNAN UNTUK PESERTA DIDIK KELAS IX SMP: PENGEMBANGAN INSTRUMEN ASSESSMENT FOR LEARNING (AFL) PADA MATERI KEKONGRUENAN DAN KESEBANGUNAN UNTUK PESERTA DIDIK KELAS IX SMP - Hidayah, Nurul; Ruslan; Dassa, Awi (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
This study aims to (1) know the development process assessment for learning (AfL) instruments on congruence and similarity subjects for grade IX junior high school students; (2) produce an assessment for learning (AfL) instruments on congruence and similarity subjects for grade IX junior high school students that are valid and reliable. This present study is development research involving 126 grade IX students of SMP Islam Athirah 2 Makassar. The results showed that: (1) the process of developing assessment for learning (AfL) instruments on congruence and similarity subject for grade IX junior high school students was carried out through the stages of compiling instrument specifications (including determining the purpose of the instrument, compiling the instrument grid, choosing the shape and format of the instrument, determining the length of the instrument, and determining the instrument scales and scoring systems), writing instruments, reviewing instruments (content validity test and instruments improvement), conducting instrument trials, interpreting measurement results, analyzing instruments (construct validity and reliability tests), and assembling instruments; (2) the results of the development of assessment for learning (AfL) instruments on congruence and similarity subject for grade IX junior high school students consisted of a learning process assessment test, a learning outcome assessment test, and a rubric for assessing cognitive aspects, psychomotor aspects, and affective aspects.